Paradox of possibilities: the rare landscape in the Asia Pacific Region - Jain, Ritu (2024)
The Asia-Pacific (APAC) region, home to 60% of the global population, has the highest number of Persons Living with a rare disease (PLWRD). To promote more equitable societies, the Asia Pacific rare disease Organization (APARDO), established in 2015, has been developing its regional position to promote collaboration, increase awareness among stakeholders, explore equitable and affordable diagnosis and treatment, and improve health outcomes and quality of life for all PLWRD. The APAC region’s heterogeneous population and complex healthcare environment pose distinctive challenges in addressing rare diseases. Through conferences, webinars, and contributions to global initiatives, APARDO is fostering connectivity and providing a platform as a part of the global rare disease (RD) community to address shared challenges. The development of APARDO to strengthen its global presence as the representative of the APAC RD region is vital for a more equitable world.